Acute flaccid paralysis due to West nile virus infection in adults: A paradigm shift entity - Boby Varkey Maramattom (Annals of Indian Academy of Neurology, 2014)
Three cases of acute flaccid paralysis (AFP) with preceding fever are described. One patient had a quadriparesis with a florid meningoencephalitic picture and the other two had asymmetric flaccid paralysis with fasciculations at the onset of illness. Magnetic resonance imaging in two cases showed prominent hyperintensitities in the spinal cord and brainstem with prominent involvement of the grey horn (polio-myelitis). Cerebrospinal fluid (CSF) polymerase chain reaction was positive for West Nile virus (WNV) in the index patient. All three cases had a positive WNV immunoglobulin M antibody in serum/CSF and significantly high titer of WNV neutralizing antibody in serum, clearly distinguishing the infection from other Flaviviridae such as Japanese encephalitis. WNV has been recognized in India for many decades; however, AFP has not been adequately described. WNV is a flavivirus that is spread by Culex mosquitoes while they take blood meals from humans and lineage 1 is capable of causing a devastating neuro-invasive disease with fatal consequences or severe morbidity. We describe the first three laboratory confirmed cases of WNV induced AFP from Kerala and briefly enumerate the salient features of this emerging threat.